The Influence Of Entrepreneurial Marketing And Marketing Performance On Competitiveness In Sendang Batik Center MSMEs, Lamongan District - Muhammad Imron Hamzah; Henny Mahmudah (Jurnal Multidisiplin Sahombu, 2024)
The sendang batik center as an area for batik craftsmen certainly requires marketing techniques as an effort to exist in the face of developments, especially the fashion sector. Entrepreneurial marketing as an alternative approach to SMEs marketing is needed to support business competitiveness both directly and through improving marketing performance. This study aims to analyze the influence of entrepreneurial marketing on the competitiveness of SMEs in the sendang batik center directly or through marketing performance. The analytica; technique used is path analysis through as structural equation mode (SEM) based on partial least square (PLS). The results showed that there was a positive influence of entrepreneurial marketing on the competitiveness and marketing performance of the sendang batim center. Significant marketing performance mediates the relationship between entrepreneurial marketing and the competitiveness of SMEsin the sendang batik center at a significance level of 10 percent.